Pengaruh locus of contol, komitmen organisasi, kinerja auditor, dan turnover intention terhadap perilaku menyimpang dalam audit (Studi Empiris Pada Kantor Akuntan Publik Di Pekanbaru dan Padang) - Desi Chairunnisa; Zulbahridar '; Rahmiati Idrus (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study aimed to examine the effect of locus of control on dysfunctional audit, the effect of organization commitment on dysfunctional audit, the effect of performance on dysfunctional audit and the effect of turnover intention on dysfunctional audit. The object of this research is independent auditors in Pekanbaru and Padang. Methods of data collection used in this research is a method of questioner. From 72 questioners distributed, returned was 62 questioners, but only 59 respondents who fill out the questioner and the method of selecting a sample using. Data analysis conducted with multiple regression model with help of software SPSS version 17.0. The result provide that locus of control, performance, and turnover intention has significant effect to the dysfunctional audit of the independent auditors in Pekanbaru and Padang. While organization commitment do not has a significant effect to the dysfunctional audit of the independent auditors in Pekanbaru and padang.Keywords : Locus of control, organization commitment, performance, turnover intention and dysfunctional audit.